Variability of Habroblattula drepanoides gen. et. sp. nov. (Insecta: Blattaria: Blattulidae) from the Yixian Formation in Liaoning, China - Wang, Tian-Tian; Liang, Jun-Hui; Ren, Dong (Zootaxa, 2007)
Habroblattula drepanoides gen. et sp. nov. (Blattulidae) is described from the Late Jurassic or Early Cretaceous sediments of the Yixian Formation in Western Liaoning, China. Wing venation of Habroblattula drepanoides reveals low coefficient of variation (CV) for total number of the forewing veins (CV=5.72) which indicates active flight capability. The higher hindwing variability (CV=14.43) might suggest Habroblattula was an advanced genus, may be caused by the regulation of the vein. The asymmetry between the left and right forewing in the same individual indicates the flight was limited when comparing with the CV of the left and right forewings.